Application of Support Vector Machine in Fault Diagnosis of Elevator Key Structures - Dou Yan (MATEC Web of Conferences, 2019)
Elevator is an important equipment in special equipment, its operation reliability is related to the life safety of elevator passengers; when the elevator fails, how to timely accurate identification of fault types and judgment of fault causes are the key to engineering application and theoretical research. This paper mainly introduces the application of support vector machine in fault diagnosis of elevator key structures.